Nucula sp. - Hryniewicz, Krzysztof; Amano, Kazutaka; Bitner, Maria Aleksandra; Hagström, Jonas; Kiel, Steffen; Klompmaker, Adiël A.; Mörs, Thomas; Robins, Cristina M.; Kaim, Andrzej (Zenodo, 2019)
? Nucula sp. Fig. 7A. Material .— One specimen (ZPAL V.48/10), poorly preserved internal mold from the upper Paleocene of Fossildalen, Spitsbergen, Svalbard. Measurements .— ZPAL V.48/10: L, 4.0 mm; H, 2.9 mm; W, 2.2 mm. Description .—Shell small, well-inflated, ovate, equivalve, inequilateral. Antero-dorsal margin long and straight, passing into rather acute anterior end; postero-dorsal margin also nearly straight, sloping steeply into bluntly pointed posterior end; ventral margin broadly arcuate. Inner side of ventral margin finely crenulate. Posterior adductor muscle scar ovate, but anterior one not visible. Hinge and pallial sinus unknown. Remarks. —The present species is similar to Nucula nucleus Linnaeus, 1758) in its shell outline and ventral crenulation. However, attribution to any particular species is not possible because the hinge could not be observed. Published as part of Hryniewicz, Krzysztof, Amano, Kazutaka, Bitner, Maria Aleksandra, Hagström, Jonas, Kiel, Steffen, Klompmaker, Adiël A., Mörs, Thomas, Robins, Cristina M. & Kaim, Andrzej, 2019, A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard, pp. 101-141 in Acta Palaeontologica Polonica 64 (1) on pages 109-110, DOI:10.4202/app.00554.2018, http://zenodo.org/record/10980900